1999
DOI: 10.1097/00005392-199911000-00080
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Mode of Action of Atp and Carbachol on Isolated Human Detrusor Smooth Muscle

Abstract: It is concluded that both agonists are equipotent in increasing intracellular Ca2+, but by different routes. The generation of purinergic contractions in detrusor from unstable bladder is not due to altered sensitivities of the detrusor myocyte to ATP or cholinergic agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…This change was not caused by a differential sensitivity of the muscle to ATP or cholinergic agonists [50]. In a follow-up paper by the same group [725], it was confirmed that the generation of purinergic contractions in detrusor strips from unstable bladders was not due to altered sensitivity of detrusor muscle to ATP. P2X1 receptor subtype expression was markedly increased in human unstable bladders [537].…”
Section: Detrusor Overactivitymentioning
confidence: 85%
“…This change was not caused by a differential sensitivity of the muscle to ATP or cholinergic agonists [50]. In a follow-up paper by the same group [725], it was confirmed that the generation of purinergic contractions in detrusor strips from unstable bladders was not due to altered sensitivity of detrusor muscle to ATP. P2X1 receptor subtype expression was markedly increased in human unstable bladders [537].…”
Section: Detrusor Overactivitymentioning
confidence: 85%
“…In rabbit and rat rabbit detrusor, ATP and acetylcholine have been proposed to cause either or both extracellular Ca 2ϩ influx and release from stores (Andersson, 1993;Munro and Wendt, 1994;Yu et al, 1996;Mimata et al, 1997). In human detrusor smooth muscle, the contribution of intracellular store release and extracellular influx to cholinergic responses often differs between studies (Andersson, 1993;Harriss et al, 1995;King et al, 1998;Masters et al, 1999;Wu et al, 1999;Visser and van Mastrigt, 2000). However, a role of extracellular Ca 2ϩ entry through dihydropyridine-sensitive Ca 2ϩ channels in the contraction induced by muscarinic and/or purinergic stimulation is generally accepted.…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…Figure 2A shows the response to carbachol, a transient increase of [Ca 2+ ] i followed by an undershoot before return to normal. This waveform has been observed in adult detrusor cells from other species (Wu and Fry 1998;Wu et al 1999), and as well as other smooth muscle cell types (Baro et al 1993) and has been suggested to be a feature of Ca 2+ release from intracellular stores. Application of 1 µM atropine completely abolished the carbachol response ( figure 2B, n=5), suggesting the action is mediated via muscarinic receptors.…”
Section: Intracellular Ca 2+ Transients From Intracellular Storesmentioning
confidence: 57%
“…(Baro et al, 1993,: Wu et al, 1999. Furthermore application of the non-hydrolysable analogue α,β-methylene ATP (ABMA), produced a similar Ca 2+ transient, suggesting that the receptor involved is P2X 1 or P2X 3 (North 2002) and abolished the response to concomitant addition of ATP ( Figure 3B).…”
Section: Intracellular Ca 2+ Transients From Intracellular Storesmentioning
confidence: 89%
See 1 more Smart Citation